The Aesthetic and Decorative Calligraphic Values ​​of the Kaaba Kiswah (The International Journal of Educational Sciences and Arts, 2024)
This study seeks to explore the aesthetic and decorative values ​​of the covering the Kaaba throughout history, focusing on design analysis. The study also aims to shed light on the genius of Arabic calligraphy embodied in the covering the Kaaba, using an analytical artistic approach and vision. The study is based on the descriptive analytical approach, The study concluded that the history of interest in designing the covering the Kaaba dates back to an ancient period before Islam, where the decorations and fabrics used developed until they reached the current form, reflecting the value of beauty and art of the covering the Kaaba through its designs, emphasizing the importance of Arab-Islamic decoration and the role of art in highlighting this. The great legacy. I also concluded that the aesthetics of Arabic calligraphy on the covering of the Kaaba express aesthetic, artistic and religious values, and carry an important message for Islam, where Arabic calligraphy is applied with the highest levels of authenticity and distinction according to artistic foundations.
Keywords: Aesthetic Values; Decorative Linear Values; Covering the Kaaba